Dampak Positif Program Kampung Zero Waste (KZW) Terhadap Kampung Yang Ada Di Kota Surabaya - Cahya Rukmana Putri; Ni Made Ida Pratiwi; Febby Rahmatullah; Anang Suhariyanto (Politeknik Kampar, 2023)
Analysis of one of the Independent Learning Campus (MBKM) programs, namely Kampung Zero Waste (KZW), which was created by the Surabaya City Government and assisted by the Surabaya City Environmental Service with the target being all villages in Surabaya. This program was created because many residents do not realize that the waste they generate will damage nature in the future, it is necessary to raise awareness among residents to understand the importance of reducing waste and disposing of it in its proper place. Through the KZW program, it is hoped that it will be able to encourage all residents of villages in the city of Surabaya and throughout Indonesia to be able to adopt a zero waste lifestyle. The KZW program was launched by the Surabaya City Environmental Service by holding a competition, namely the Kampung Surabaya Hebat (KSH) related to the KZW program. This competition is held for villages throughout Surabaya, so that all village residents work together to improve their villages and take various ways to reduce waste in their villages. There are many ways to reduce waste, such as making natural composters, ecobricks, recycling, waste banks and many more. The research was conducted to determine the positive impact of the KZW program on villages in the city of Surabaya.